2014
DOI: 10.1007/s10801-014-0557-y
|View full text |Cite
|
Sign up to set email alerts
|

The graphs with all but two eigenvalues equal to  $$\pm 1$$ ± 1

Abstract: We determine all graphs whose adjacency matrix has at most two eigenvalues (multiplicities included) different from ±1 and decide which of these graphs are determined by their spectrum. This includes the so-called friendship graphs, which consist of a number of edge-disjoint triangles meeting in one vertex. It turns out that the friendship graph is determined by its spectrum, except when the number of triangles equals sixteen.Computing det(Q + I) and det(Q − I) shows that Q has no eigenvalue −1, and Q has an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 7 publications
1
60
0
2
Order By: Relevance
“…To be more clear, let G denote the family of connected non-bipartite graphs all of whose eigenvalues are contained [−1, 1] except the largest and smallest ones. As mentioned before, in this article, we will completely describe the family G. This generalizes the main result of [5].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…To be more clear, let G denote the family of connected non-bipartite graphs all of whose eigenvalues are contained [−1, 1] except the largest and smallest ones. As mentioned before, in this article, we will completely describe the family G. This generalizes the main result of [5].…”
Section: Introductionmentioning
confidence: 60%
“…In [4], van Dam and Spence described the connected bipartite graphs with all but two eigenvalues in {−1, 1}. Very recently, Cioabȃ et al [5] explicitly determined the connected non-bipartite graphs with all but two eigenvalues in {−1, 1}.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is good to mention that Cioabȃ, Haemers, Vermette, and Wong [6] recently showed that all Friendship graphs except the one on 33 vertices are determined by the spectrum. These graphs also have four distinct eigenvalues of which two are simple, just like the non-regular graphs in a regular two-graph.…”
Section: Theorem 52 For Every Integer T There Exists a Connected Nmentioning
confidence: 98%
“…It is claimed in [8] that conjecture is valid. In [7], it is proved that if Γ is any graph cospectral with F n (n = 16), then Γ ∼ = F n . Abdollahi and Janbaz [3] precented a proof in special case of this topic.…”
Section: Introductionmentioning
confidence: 99%